1998
DOI: 10.1007/s001050050743
|View full text |Cite
|
Sign up to set email alerts
|

Mometason und Calcipotriol optimieren den therapeutischen Initialeffekt von Dithranol auf die chronisch stationäre Psoriasis (CSP)

Abstract: In a randomized study 30 patients with chronic stationary psoriasis were treated with 3 different topical schemes. Group 1 (n = 10) received monotherapy (dithranol (D) twice a day, D/D), group 2 (n = 10) calcipotriol mornings/dithranol evenings (calcipotriol (C)/dithranol (D) C/D) and 3 (mometasone (M) mornings/dithranol (D) evenings, M/D). During the therapy period of 4 weeks we documented the PASI-Score as well as infiltration, erythema and desquamation weekly. The M/D group revealed in the first week a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
7
1
1
Order By: Relevance
“…Therefore, it seems reasonable to assume that calcipotriol is capable of causing a continuous augmentation of the antipsoriatic effects of dithranol that leads to a rapid healing of psoriatic plaques with a significant reduction in the length of the treatment period and consequently to a better patient compliance. The discrepancy between our results and those of Sander et al [17] is most probably due to the obvious marked differences in the design and methods of the two studies. Table 3 summarizes the data originating from a group of inpatients with chronic plaque psoriasis (with PASI scores comparable with those of the patients of the present study) who had been treated in our Department with calcipotriol (ointment) monotherapy for 6 weeks.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Therefore, it seems reasonable to assume that calcipotriol is capable of causing a continuous augmentation of the antipsoriatic effects of dithranol that leads to a rapid healing of psoriatic plaques with a significant reduction in the length of the treatment period and consequently to a better patient compliance. The discrepancy between our results and those of Sander et al [17] is most probably due to the obvious marked differences in the design and methods of the two studies. Table 3 summarizes the data originating from a group of inpatients with chronic plaque psoriasis (with PASI scores comparable with those of the patients of the present study) who had been treated in our Department with calcipotriol (ointment) monotherapy for 6 weeks.…”
Section: Discussioncontrasting
confidence: 57%
“…In a recent open clinical trial, Sander et al [17] reported that addition of calcipotriol ointment (once daily) to conventional dithranol application results in an enhancement of the therapeutic efficacy of the latter in chronic plaque psoriasis only in the initial phase of the treatment, whereas by the end of the trial, no significant differences were found by these authors between the combined regimen and dithranol monotherapy with regard to therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 86%
“…Two other papers concluded that the combination of dithranol with a mid‐potent 47 or with a potent corticosteroid 46 respectively showed no significant differences compared to dithranol monotherapy. In the latter open clinical study 46 dithranol monotherapy was compared to combination therapy of dithranol with mometasone and to a combination regimen with dithranol and calcipotriol ointment. Adding calcipotriol to conventional dithranol application resulted in an enhancement of the therapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Literature search revealed eight studies on the combination of dithranol and topical corticosteroids [41][42][43][44][45][46][47][48] and two on dithranol combined with vitamin D analogues. 46,49 Three papers were excluded because results were on other types of psoriasis and other localized skin diseases, 41,44,45 one because demographic data were lacking, 48 and one paper was excluded because the treatment strategy was unclear. 43 Results show that the added value of a topical corticosteroid to dithranol therapy is related to steroid-potency.…”
Section: Dithranol Combined With Topical Corticosteroids or Vitamin Dmentioning
confidence: 99%
“…One factor that is common to these topical agents is a significant potential for causing irritation [1]. It has been proven possible to reduce the risk of such undesirable effects by combining various topical agents or topical and systemic antipsoriatics and, at the same time, to reduce the costs of treatment [2, 3, 4]. …”
Section: Introductionmentioning
confidence: 99%